1998
DOI: 10.1046/j.1471-4159.1998.71062505.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Increases β‐Amyloid Peptide 1‐42 in Cerebrospinal Fluid

Abstract: The β‐amyloid peptides, Aβ1‐42 and Aβ1‐40, were quantified in ventricular CSF taken daily for up to 3 weeks from six individuals with severe traumatic brain injury (TBI). There was considerable interindividual variability in the levels of Aβ peptides, but in general Aβ1‐42 levels equalled or exceeded those of Aβ1‐40. Averaging the daily totals of our trauma cohort revealed that the levels of Aβ1‐42 and Aβ1‐40 rose after injury, peaking in the first week and then declining toward control levels over the next 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…Indeed, Aβ containing plaque-like structures have been identified in brain injured tissue just hours after trauma, often close to damaged axons (17,20,37,44). Additionally, elevated Aβ peptide has been identified in the cerebrospinal fluid of TBI cases (11,35). Our data suggest that the anabolism of Aβ remains elevated in axons both acutely and up to 3 years after trauma.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, Aβ containing plaque-like structures have been identified in brain injured tissue just hours after trauma, often close to damaged axons (17,20,37,44). Additionally, elevated Aβ peptide has been identified in the cerebrospinal fluid of TBI cases (11,35). Our data suggest that the anabolism of Aβ remains elevated in axons both acutely and up to 3 years after trauma.…”
Section: Discussionmentioning
confidence: 56%
“…While apolipoprotein E e4 allele is the best-documented genetic risk factor for SAD (Corder et al 1993;Saunders et al 1993;Strittmatter et al 1993), traumatic brain injury (TBI) represents the most robust environmental AD risk factor (Schofield et al 1997;Nemetz et al 1999;Plassman et al 2000;Jellinger et al 2001). TBI has been shown to induce an increase in cerebrospinal fluid (CSF) Ab levels (Raby et al 1998), as well as Ab deposition in the human brain (Nicoll et al 1995), and Ab plaques have been found within days after a single incident of TBI in humans (Roberts et al 1991;Graham et al 1995). However, recent conflicting results have also been reported (Franz et al 2003;Kay et al 2003).…”
mentioning
confidence: 99%
“…This apparent link between TBI and AD stimulated investigation into potential mechanisms underlying the association, and the most carefully studied pathophysiological mechanism is the production and clearance of amyloid-β (Aβ) after TBI [19]. However, studies of Aβ peptide levels in humans with TBI have produced contradictory results [20,21]. Additional research has demonstrated increased levels of hyperphosphorylated tau protein, the same protein involved in the NFTs in AD, are found in individuals who have experienced a severe TBI [22]; however, it remains unclear whether or how TBI-associated plaques identified acutely after injury develop into the dense neuritic plaques that are the hallmark pathological features of AD.…”
Section: Future Perspective: Implications For Patient Carementioning
confidence: 99%